The Process of Economic Development in West Sichuan: The Case of Daocheng County - Carsten A. Holz (Center for Economic Studies and ifo Institute (CESifo), 2020)
Economic development of a remote, mountainous region is a challenge for any country. This paper examines how this development challenge has been addressed in a high-altitude backward region of the People's Republic of China. Is this region increasingly being left behind or has it entered a sustainable development trajectory? What form does economic development take? What is the role of the government vs. the private sector? What are the broader socio-economic and cultural consequences? The focus is on Daocheng County, Ganzi Tibetan Autonomous Region, West Sichuan. The fact that it is a predominantly Tibetan county adds a nationality dimension to the issue of economic development.
Keywords: O12; O23; O25; O53; L83; Z32; 330; economic development; tourism development; infrastructure development; poverty alleviation; backward region; fiscal transfers; Tibet